Desert Storm air war : the aerial campaign against Saddam's Iraq in the 1991 Gulf War - Corrigan, Jim (Guilford, Connecticut : Stackpole Books, 2017)
The air campaign that opened the Gulf War in January 1991 was one of the most stunning in history. More than 100,000 sorties were launched as American and other Coalition aircraft pounded enemy targets with 88,000 tons of bombs. This book reconstructs events through the eyes of the strategists who planned it and the pilots who flew the missions.
Part I. Desert Shield -- Seeds of crisis -- Deployment -- Turbulence -- Instant thunder -- Black hole -- Part II. Desert Storm -- Leading edge -- First in -- Attack of the machines -- Bogeys and bandits -- Luck runs out -- Low level -- Basra raid -- Pain and suffering -- Package Q -- Eagles go hunting -- Great Scud hunt -- Search and rescue -- Desperation -- Bag of tricks -- Taking shelter -- Khafji -- Preparing the battlefield -- Kill box -- Missteps -- Close calls -- Part III. Airpower in the ground war -- Left hook -- Twenty-three tanks -- Missiles and misfortune -- Waning hours -- Vague victory.
Includes index.
Keywords: MILITARY CAMPAIGNS